Quasinormal modes of regular black holes with sub-Planckian curvature and Minkowskian core - Chen Tang; Yi Ling; Qing-Quan Jiang; Guo-Ping Li (European Physical Journal C: Particles and Fields)
Abstract We investigate the perturbation of the scalar field as well as the electromagnetic field over a sort of regular black holes which are characterized by the sub-Planckian curvature and the Minkowskian core. Specifically, we compute the quasinormal modes (QNMs) by employing the pseudo-spectral method. The outburst of overtones is manifestly observed in the QNMs of these regular black holes, which can be attributed to the deviation of the Schwarzschild black hole by quantum effects of gravity. Furthermore, the QNMs under the perturbation of electromagnetic field exhibit smaller real and imaginary parts than those under scalar field perturbation. By comparing the QNMs of the regular black hole featured by Minkowskian core with those of Bardeen black hole featured by de Sitter core, we find they may be an effective tool to distinguish these BHs.